Easy Room Temperature Synthesis of High Surface Area Anatase Nanowires with Different Morphologies - Christopher Schneider; Dr. Ning Liu; Dr. Stefan Romeis; Prof. Dr. Wolfgang Peukert; Prof. Dr. Patrik Schmuki (ChemistryOpen, 2019)
Abstract Anatase nanowires were synthesized in solution by using a simple mixing of titanium diisopropoxide bis(acetylacetonate), lactic acid and sodium hydroxide at room temperature. We discuss effects of reaction parameters and post treatment (annealing) on the nanowire morphology, surface area, and crystallinity, as well as the competing morphology directing effects of lactic acid and sodium hydroxide. Then the room temperature nanowires were directly grown onto fluoride doped tin oxide (FTO) glass to form photoanodes. Photoelectrochemical measurements of the different nanowires were performed and compared to conventional nanowires produced by high temperature synthesis. Clearly the nanowires introduced in this work show a significant increase in the maximum photocurrent, compared to classic hydrothermal nanowire layers.